A retrospective study on clinician’s practice on testing and treating for cytomegalovirus infection in patients with acute ulcerative colitis in a tertiary care center in India - Kumar, Ajay; Mohindra, Samir; Deep, Amar; Atam, Virendra; Chandra, Abhijit (International Journal of Research in Medical Sciences, 2017)
Background: Reactivation of cytomegalovirus (CMV) may occur in patients with ulcerative colitis (UC) while on immunosuppressive treatment. Whereas some workers suggested that treatment of CMV is needed in them, others contradicted this. We aimed to retrospectively evaluate, a) how frequently clinicians evaluate for CMV in patients admitted with acute severe colitis, b) prevalence of its occurrence, and c) how frequently clinicians treated CMV infection in a tertiary care center. Methods: Data on consecutive patients with UC admitted to the department of Gastroenterology during a seven-year period at a tertiary care center were retrospectively reviewed. Frequency of evaluation for CMV (IgM antibody, polymerase chain reaction or inclusion body in H and E-stained sections by the treating clinicians was evaluated. Any one test positive out of all the three tests was considered as evidence of CMV infection. Frequency of treatment directed against CMV by treating clinicians was evaluated. Results: Among 181 admitted patients with UC, 41 (22.6%) were tested for CMV infection, of whom 28 (59.6%) were male. Fourteen of 41 (34.1%) were CMV positive (one of three above mentioned tests positive). Twelve had detectable CMV DNA by PCR and 3 had IgM antibody positive (one of whom also had inclusion body on histopathology). Three of 14 patients with CMV infection received anti-viral treatment (ganciclovir in two, ganciclovir followed by valganciclovir in one). Conclusions: These data suggest that investigating and treating CMV as a cause for acute ulcerative colitis is becoming obsolete About one-fourth of patients admitted with severe UC in a tertiary centre are screened for CMV infection, about one-third of whom tested positive to at least one test. Only one-fifth of patients with positive result to the test were treated against the infection.